2018
DOI: 10.1148/radiol.2018180285
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Patients with Cardiac Implantable Electronic Devices

Abstract: Indications for MRI have grown considerably in recent years. However, many patients with cardiac implantable electronic devices are denied imaging due to physician misinterpretation of the risks associated with MRI. This review discusses the theoretical basis for the perceived risk by exploring preclinical literature. It then presents a detailed examination of the true rates of adverse events in clinical studies across both MR nonconditional (legacy) and MR conditional devices. Indeed, many of these adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 83 publications
2
73
0
15
Order By: Relevance
“…A complete ISO TS 10974 industry-standard guidelines for implant testing of the safety of the proposed µMS implant is lacking, and further MRI safety analysis is necessary (ISO/TS 10974, 2012;Cabot et al, 2013) before this technology is translated into the clinics. Further simulations on a finalized lead design with models that include all possible implant pathways and measurements with RF injection in the implant (Muthalaly et al, 2018;Brown et al, 2019) to simulate the exposure scenarios inside the scanner, as well as heating tests, will be required on the final implant. These tests are required by the FDA to ensure the worst-case scenario sufficiently meets the requirements for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…A complete ISO TS 10974 industry-standard guidelines for implant testing of the safety of the proposed µMS implant is lacking, and further MRI safety analysis is necessary (ISO/TS 10974, 2012;Cabot et al, 2013) before this technology is translated into the clinics. Further simulations on a finalized lead design with models that include all possible implant pathways and measurements with RF injection in the implant (Muthalaly et al, 2018;Brown et al, 2019) to simulate the exposure scenarios inside the scanner, as well as heating tests, will be required on the final implant. These tests are required by the FDA to ensure the worst-case scenario sufficiently meets the requirements for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta-analysis showed that late gadolinium enhancement on cardiac MRI is considerably correlated with ventricular arrhythmic events in the patients with ischemic or nonischemic CMP [OR 5.62 (95% CI: 4.20-7.51)] (12). In myocarditis, MRI has a poor sensitivity at the early stages of the disease; therefore, both im- (13,14). However, artifacts resulting from such cardiac devices may adversely affect the visualization of myocardial abnormalities.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Software modifications with an BMRI mode^were introduced so reprogramming before and after scanning became straightforward and electromagnetic interference minimized. Since their approval in 2008, multiple studies and over 10,000 scans have demonstrated their safety, and are detailed elsewhere [7,12].…”
Section: New Technologymentioning
confidence: 99%
“…Historically, MRI has been contraindicated for safety but each of these individuals has an estimated need for MRI in their lifetime of 50-75%, particularly because they are older and have more comorbidities [6]. Now, technical developments have made it reasonable to perform MRI for these individuals [7], but provision remains grossly inadequate due to logistical difficulties. This review therefore discusses the significant non-technical barriers to developing a sustainable service.…”
Section: Introductionmentioning
confidence: 99%